Force Feed Effects on Process Stability in Turning (Bangladesh Journal of Scientific and Industrial Research, 2010)
This paper presents analytical stabiltity analysis of turning using non-linear force-feed model in two dimensions. Most of the existing analytical models ignored the effect of static feed term on the regeneration phenomenon. In practice there is a marked effect of feed on stability due to force variation. The modified analytical equations for cutting insert using three dimensional too geometry are obtained by considering relative motion of tool with respect to a two dimensional elastic model of work-piece. The critical stability limits obtained as a function of feed are confirmed with time domain analysis. Experiments are conducted on a flexible work-piece at varying feed conditions. The measured cutting forces show a marked effect of feed on stability. A neural network models developed to obtain the critical depth of cut at various values of operating speeds and feeds. Key words: Dynamics modeling; Tool geometry; Force-feed; Stab. DOI: 10.3329/bjsir.v45i2.5710Bangladesh J. Sci. Ind. Res. 45(2), 129-132, 2010